DUAL ETHICS IN ROMANS 13 - Iwasa, Noriaki (Journal of Dharma, 2010)
Seemingly Rom 13 demands the people’s unconditional submission to the state.[1] But what if the state’s policy contradicts God’s teachings? I first survey various answers to the problem. As we will see, those answers assume that what is morally wrong for the state to order is morally wrong for the people to follow. I argue, however, that there can be cases where a state’s policy is morally wrong while the people’s submission to it is morally right. I distinguish between the ethical standards for the state and those for the people. I point out the following: The dual ethics protects conscientious people from moral blame for having obeyed the authority. The dual ethics makes it impossible to appeal to Rom 13 to justify tyranny. The dual ethics is also compatible with the various answers. Finally, I show that some New Testament passages support the dual ethics.